Resemblance metaphor and metonymy in the ethnozoological lexicon of the Amazonian language Aguaruna - García Ruiz, Ketty; Huasco Escalante, Jaime; López Rojas, Jhon Jairo (De Gruyter Mouto, 2025)
This chapter focuses on the analysis of resemblance metaphors and metonymies that operate in the ethnozoological lexicon of the Amazonian language Aguaruna. Our corpus is basically composed of binomials (noun-noun compounds) in which these semantic mechanisms are representative and useful for naming sub-generic species. In our analysis, we have mostly identified the mapping of prominent characteristics such as color and shape (metonymic bases) in resemblance metaphors. Many of our examples also reveal the preference for metonymies constituted by habitat data and the diet of the named entities, significant information for a hunting people like the Aguaruna. Finally, we see that, in the binomials analyzed, the source domains are not always other biological organisms (plants and animals), but can be elements of nature, cultural objects, and even mythological characters.